(untitled) (Clinics, 2013)
Renal dysfunction is common during episodes of acute decompensated heart failure, and historical data indicate that the mean creatinine level at admission has risen in recent decades. Different mechanisms underlying this change over time have been proposed, such as demographic changes, hemodynamic and neurohumoral derangements and medical interventions. In this setting, various strategies have been proposed for the prevention of renal dysfunction with heterogeneous results. In the present article, we review and discuss the main aspects of renal dysfunction prevention according to the different stages of heart failure.